Comparison of procedure-related complications between percutaneous cryoablation and radiofrequency ablation for treating periductal hepatocellular carcinoma. (1st January 2020) - Ko, Seong Eun; Lee, Min Woo; Rhim, Hyunchul; Kang, Tae Wook; Song, Kyoung Doo; Cha, Dong Ik; Lim, Hyo Keun
Abstract: Purpose: This study aimed to evaluate the incidence and severity of biliary complications after treating periductal hepatocellular carcinomas (HCCs) using either cryoablation (CA) or radiofrequency ablation (RFA) and assess independent risk factors for biliary complications after treatment. Materials and methods: Between July 2008 and August 2018, 949 patients with treatment-naïve HCCs underwent either RFA or CA in our institution. Of these, patients with multiple HCCs, tumors equal to or larger than 3 cm or smaller than 1 cm, and tumors with non-periductal locations were excluded. Finally, 31 patients and 25 patients were included in the RFA group and the CA group, respectively. The incidence and severity of biliary complications were compared between the RFA and CA groups. The risk factors for biliary complications were assessed using univariable and multivariable logistic regression analyses using the following variables: age, sex, tumor size, Child–Pugh score, tumor location (peripheral duct versus central duct), ablation method (RFA versus CA), the number of applicators, ablation time, and ablation volume. Results: The incidence and severity of biliary complications were significantly higher in the RFA group than in the CA group ( p = 0.007 and p = 0.002, respectively). In univariable and multivariable analyses, the ablation method was an independent risk factor for biliary complications ( p = 0.004 and 0.013, respectively). Conclusions: The incidence and severity of biliary complications after treating HCCs abutting the bile duct are lower in CA than RFA, demonstrating that CA is safer than RFA for ablating small periductal HCCs.